Administration Model Development of Local Administrative Organization Administrators under the Good Governance Principles in Surat Thani Province - Chaisamut, Anak; Phuakkong, Chaiwat; Wangukkarangkul, Amorn (Rajapark Journal, 2022)
The objectives of this research were to: 1) study the characteristics of the administrators of local administrative organizations; 2) analyze the factors promoting administration according to good governance; and 3) develop a model of administration by good governance for the administrators of local administrative organizations in Surat Thani Province. Using a mixed-methods research methodology, quantitative analysis used a questionnaire with 400 respondents. Descriptive statistics were used: frequency, percentage, mean, and standard deviation; factor analysis; structural equation model analysis; and qualitative analysis using in-depth interviews with key informants. It was found that 1) the characteristics of the local administrative organization’s administrators overall were at a high level, considering each aspect, and that participation, responsibility, value, transparency, the rule of law, and morality were at the highest averages, respectively. 2) Factors promoting administration according to good governance overall, at a high level considering each aspect, found that personality, administration, official performance, and planning were at the highest averages, respectively. The result of the model consistency test found that the model was consistent with the empirical data. and 3) the management, according to the principles of good governance of local administrative organization administrators, must use a professional management style consisting of planning, government operations, personality, and administration that causes the principles of good governance of administrators in local government organizations in Surat Thani Province.